Genome-wide identification, characterization and expression analysis of the HD-Zip gene family in the stem development of the woody plant Prunus mume - Li, Lulu; Zheng, Tangchun; Zhuo, Xiaokang; Li, Suzhen; Qiu, Like; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (PeerJ, 2019)
The homeodomain-leucine zipper (HD-Zip) gene family, a group of plant-specific transcriptional factors (TFs), participates in regulating growth, development, and environmental responses. However, the characteristics and biological functions of HD-Zip genes in Prunus mume, which blooms in late winter or early spring, have not been reported. In this study, 32 HD-Zip genes, named PmHB1–PmHB32 based on their chromosomal positions, were identified in the genome of P. mume. These genes are distributed among seven chromosomes and are phylogenetically clustered into four major groups. Gene structure and motif composition were mostly conserved in each group. The Ka/Ks ratios showed that purifying selection has played a leading role in the long-term evolution of the genes, which maintained the function of this family. MicroRNA target site prediction indicated that the genes of the HD-Zip III subfamily may be regulated by miR165/166. Expression pattern analysis showed that the 32 genes were differentially expressed across five different tissues (leaf, flower bud, stem, fruit, and root) and at different stages of stem and leaf-bud development, suggesting that 10 of the genes may play important roles in stem development. Protein–protein interaction predictions showed that the subfamily III genes may regulate vascular development and shoot apical meristem (SAM) maintenance. Promoter analysis showed that the HD-Zip III genes might be involved in responses to light, hormones, and abiotic stressors and stem development. Taken together, our results provide an overview of the HD-Zip family in P. mume and lay the foundation for the molecular breeding of woody ornamental plants.
Keywords: Prunus mume; Genetic evolution; Expression pattern; Stem development; HD-Zip TFs